Inflammasomes and Cardiovascular Disease: Linking Inflammation to Cardiovascular Pathophysiology - Saadh, Mohamed J.; Muhammad, Faris Anad; Albadr, Rafid Jihad; Sanghvi, Gaurav; Jyothi, S. Renuka; Kundlas, Mayank; Joshi, Kamal Kant; Rakhmatullaev, Akmal; Taher, Waam Mohammed; Alwan, Mariem; Jawad, Mahmood Jasem; Ali Al‐Nuaimi, Ali M. (Scandinavian journal of immunology, 2025)
ABSTRACT Cardiovascular diseases (CVDs) remain a leading cause of global mortality, driven by risk factors such as dyslipidemia, hypertension and diabetes. Recent research has highlighted the critical role of inflammasomes, particularly the NLRP3 inflammasome, in the pathogenesis of various CVDs, including hypertension, atherosclerosis, myocardial infarction and heart failure. Inflammasomes are intracellular protein complexes that activate inflammatory responses through the production of pro‐inflammatory cytokines such as IL‐1β and IL‐18, contributing to endothelial dysfunction, plaque formation and myocardial injury. This review provides a comprehensive overview of the structure, activation mechanisms and pathways of inflammasomes, with a focus on their involvement in cardiovascular pathology. Key activation pathways include ion fluxes (K+ efflux and Ca2+ signalling), endoplasmic reticulum (ER) stress, mitochondrial dysfunction and lysosomal destabilisation. The review also explores the therapeutic potential of targeting inflammasomes to mitigate inflammation and improve outcomes in CVDs. Emerging strategies include small‐molecule inhibitors, biologics and RNA‐based therapeutics, with a particular emphasis on NLRP3 inhibition. Additionally, the integration of artificial intelligence (AI) in cardiovascular research offers promising avenues for identifying novel biomarkers, predicting disease risk and developing personalised treatment strategies. Future research directions should focus on understanding the interactions between inflammasomes and other immune components, as well as genetic regulators, to uncover new therapeutic targets. By elucidating the complex role of inflammasomes in CVDs, this review underscores the potential for innovative therapies to address inflammation‐driven cardiovascular pathology, ultimately improving patient outcomes. Inflammasomes, particularly NLRP3, play a critical role in cardiovascular diseases by driving inflammation and contributing to conditions like atherosclerosis, myocardial infarction and heart failure. This review highlights their activation mechanisms, therapeutic targeting and the potential of AI‐driven approaches to improve diagnosis and treatment of inflammation‐driven cardiovascular pathology.